The maturity of delinquent and non-delinquent adolescents as defined by the developmental task concept - Mitchell, Irving Eugene (1957)
Thesis (Ph.D.)--Boston UniversityI. STATEMENT OF THE PROBLEM Purposes. The purposes of this study are: (1) to evaluate and compare the maturity of adolescent delinquents and non-delinquents as defined by the developmental task concept; (2) to study and evaluate the relationship that exists between adolescent maturity as defined above and social adjustment as measured by the Washburne Social-Adjustment Inventory; (3) to examine the relationship that exists between intelligence as measured by standard IQ tests, and maturity; and (4) to assess the relationship that exists between maturity and occupational prestige of parents, as measured by the North-Hatt Scale. Major Hypothesis. Stated in null form, there is no significant difference in the maturity of adolescent delinquents and non-delinquents as defined by the developmental task concept. Subsidiary Hypotheses. Stated in null form, (1) there is no significant relationship between maturity and occupational prestige of the samples' parents; (2) there is no significant relationship between maturity and social adjustment; (3) there is no significant relationship between maturity and intelligence; (4) there is no significant difference in the maturity of adolescent boys and girls, delinquent or non-delinquent. II. PROCEDURE OF THE STUDY Subjects. The subjects compared consist of two groups: non-delinquent and delinquent. The non-delinquent group is composed of 505 students in the ninth grades of the four Junior High Schools of Newark, Ohio, and students of the ninth grades of the Washington-Utica High School. The delinquent group is composed of 187 students in the ninth grades of the Boys Industrial School, Lancaster, Ohio, and the Girls Industrial School, Delaware, Ohio. Methods. The hypotheses were tested by administering the following instruments: (1) the McCleery Scale of Adolescent Development designed to measure maturity, as defined by the developmental task concept, (2) the Washburne Social-Adjustment Inventory designed to measure social adjustment, (3) the North-Hatt Scale designed to measure occupational prestige, and (4) standardized intelligence tests. The data were analyzed by means of standard statistical techniques to determine if significant differences or relationships existed between the scores of the delinquent and non-delinquent subjects. Other methods used were unstructured interviews, formal questionnaries and observation. III. RESULTS AND CONCLUSIONS Major Hypothesis. No significant difference between delinquent and non-delinquent Total Maturity scores was found at the 5% level when the "t" test was applied. Significant differences were found between the scores of delinquent and non-delinquent girls on the subtests, Occupational Preparation and Family Life. The difference in the Family Life score was found to be the result of a tautology. A significant difference was found between delinquent and non-delinquent boys on the subtests, Social Role and Civic Competence. The difference in the Civic Competence score was found to be partially the result of the delinquents' unique experience with professionally trained people. The conclusion was reached that delinquent boys and girls are similar in total maturation to non-delinquent boys and girls and that total maturity, per se, is not an important factor in delinquency. However, lack of maturity in an essential task or tasks may result in delinquency. Subsidiary Hypotheses. (1) The relationship existing between occupational prestige ratings of parents and Total Maturity scores of their children is negligible. (2) No significant relationship between maturity and social adjustment was found to exist for either of the samples. (3) The relationship existing between maturity and intelligence was found to be negligible. (4) It was concluded that as far as the developmental tasks are concerned, the boys, delinquent and non-delinquent were more mature in most instances than the girls